Modeling and Control System Design of a Cascade Vapor Compression System - Jarhult, Casper (My University, 2025)
This thesis investigates the modeling, simulation, and analysis of a cascade va por compression system designed for aerospace thermal management, delivering a 25 kW cooling capacity. Control design focuses on maintaining a liquid coolant at 20 ◦C, ensuring 5 ◦C superheat at the evaporator outlets, and an intermediate temperature set to the geometric mean of the low-stage evaporator and high-stage condenser to enhance system efficiency. PI controllers are incorporated to regu late performance under various operating conditions. A MATLAB Simscape model was developed using R134a for the low stage and R1233zd(E) for the high stage, enabling performance evaluation across a range of ambient temperatures and heat loads. Simulations demonstrate that the cascade configuration can maintain stable coolant temperatures across a wide range of ambient conditions, as well as sufficient superheat at the evaporator outlets. The use of the geometric mean for selecting the intermediate pressure ratio proved effective, though not optimal, as evidenced by variations in compressor power input between the low- and high-stage cycles. However, limitations were identified at low ambient temperatures, where evaporator and condenser pressures converge, causing instability in superheat control. Addi tional challenges were observed at low heat loads, where controller performance was sensitive to tuning, resulting in oscillations. These results demonstrate the viability of cascade vapor compression systems for demanding aerospace thermal manage ment tasks, while highlighting challenges related to low-temperature operation and controller robustness that require further investigation.
Keywords: Vapor Compression System, Cascade System, Refrigeration, Simulink, Simscape.